(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Peliococcus chersonensis (Kiritshenko), Trionymus radicum (Newstead) (Pseudococcidae), Stotzia ephedrae (Newstead) (Coccidae) and Quadraspidiotus mairei (Balachowski) (Diaspididae) are recorded for the first time in Italy. New distributional data are reported for Chaetococcus sulcii (Green), Peliococcus manifectus Borchsenius, Phenacoccus asphodeli Goux, Dysmicoccus multivorus (Kiritshenko), Volvicoccus volvifer (Goux) (Pseudococcidae), Protopulvinaria pyriformis Cockerell (Coccidae), Aspidiotus spinosus Comstock, Chionaspis lepineyi Balachowsky, Dynaspidiotus ephedrarum (Lindinger), Adiscodiaspis ericicola (Marchal), Rungaspis capparidis (Bodenheimer) (Diaspididae).